2016
DOI: 10.1007/s00167-016-4368-7
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant coracoplasty during arthroscopic subscapularis repair does not yield better clinical outcomes and structural integrity

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
(65 reference statements)
0
22
1
4
Order By: Relevance
“…At the second-year follow-up, all functional scores improved significantly in both groups compared to preoperative values although, similar to our study, no significant difference was found between the study and control groups. In Kim et al's study, [16] the preoperative mean UCLA score was 16.8 for group 1 and 16.4 for group 2 and the postoperative mean UCLA scores were 31.3 and 31.5, respectively, compared to the preoperative mean UCLA scores of 19.6 and 20.4 and postoperative mean UCLA scores of 27.9 and 29.3 in our study. On the other hand, Kim et al [16] included Lafosse type 4 tears in their study whereas, in our study, only type 2 and 3 tears were evaluated, so that fatty infiltration did not have an impact on clinical outcomes.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…At the second-year follow-up, all functional scores improved significantly in both groups compared to preoperative values although, similar to our study, no significant difference was found between the study and control groups. In Kim et al's study, [16] the preoperative mean UCLA score was 16.8 for group 1 and 16.4 for group 2 and the postoperative mean UCLA scores were 31.3 and 31.5, respectively, compared to the preoperative mean UCLA scores of 19.6 and 20.4 and postoperative mean UCLA scores of 27.9 and 29.3 in our study. On the other hand, Kim et al [16] included Lafosse type 4 tears in their study whereas, in our study, only type 2 and 3 tears were evaluated, so that fatty infiltration did not have an impact on clinical outcomes.…”
Section: Discussioncontrasting
confidence: 48%
“…The superiority of our study to this study was that the study and control groups were composed of patients with isolated subscapularis tear and subcoracoid impingement. Kim et al [16] assessed 62 patients who underwent isolated arthroscopic subscapularis repair and compared patients who underwent or did not undergo coracoplasty. At the second-year follow-up, all functional scores improved significantly in both groups compared to preoperative values although, similar to our study, no significant difference was found between the study and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…En las lesiones asociadas, como en la del tendón de la PLB (luxaciones o subluxaciones), es recomendable realizar una tenotomía o tenodesis (27)(28)(29) y, si el espacio coracohumeral es menor de 7 mm, realizar una coracoplastia para proteger la sutura del subescapular (2,36) . Asimismo, la reparación de las lesiones del resto del manguito rotador mejoran la función del hombro y dan más resistencia a la reparación del tendón del subescapular (3) .…”
Section: Discussionunclassified
“…En lesiones que afectan al tercio superior se considera que un anclaje es suficiente, pero las que afectan al 100% de la inserción necesitarían 2 anclajes (2,35) . La indicación de coracoplastia varía según diferentes autores y se recomienda cuando la distancia coracohumeral es menor de 7-10 mm (2,36) . En este artículo exponemos nuestra experiencia en el diagnóstico, el tratamiento y los resultados obtenidos en la sutura del tendón del subescapular mediante técnica artroscópica.…”
Section: Introductionunclassified
“…Diversos autores mostram que a diminuição do intervalo coracoumeral pode ser fator causal para roturas do subescapular e indicam a coracoplastia nestes casos 38,65,[79][80][81][82][83] . Por outro lado, existem alguns estudos na literatura que demonstram não haver correlação entre rotura do subescapular e intervalo coracoumeral reduzido e nenhuma evidência de melhora da integridade do subescapular após realização de coracoplastia associada a reparo do mesmo 84,85 . Revelam ainda que casos de reparo do subescapular isolado ou associado com reparo do supraespinal sem a realização de coracoplastia evidenciam resultados funcionais bons e com baixo índice de rerrotura 5,84,86,87 .…”
Section: Rmunclassified